High MMP‐9 activity levels in fragile X syndrome are lowered by minocycline. Issue 8 (3rd July 2013) - Dziembowska, Magdalena; Pretto, Dalyir I.; Janusz, Aleksandra; Kaczmarek, Leszek; Leigh, Mary Jacena; Gabriel, Nielsen; Durbin‐Johnson, Blythe; Hagerman, Randi J.; Tassone, Flora
Abstract Fragile X syndrome (FXS) is a neurodevelopmental disorder characterized by lack of the FMR1 protein, FMRP, a translational repressor. Its absence leads to up‐regulation of locally translated proteins involved in synaptic transmission and plasticity, including the matrix metalloproteinase‐9 (MMP‐9). In the Fmr1 knock‐out (KO), a mouse model of FXS, an abnormal elevated expression of MMP‐9 in the brain was pharmacologically down‐regulated after treatment with the tetracycline derivative minocycline. Moreover, the rescue of immature dendritic spine morphology and a significant improvement of abnormal behavior were associated with down‐regulation of MMP‐9. Here, we report on high plasma activity of MMP‐9 in individuals with FXS. In addition, we investigate MMP‐9 changes in patients with FXS who have gone through a minocycline controlled clinical trial and correlate MMP‐9 activity to clinical observations. The results of this study suggest that, in humans, activity levels of MMP‐9 are lowered by minocycline and that, in some cases, changes in MMP‐9 activity are positively associated with improvement based on clinical measures. © 2013 Wiley Periodicals, Inc.